Psychosocial Treatments for Child and Adolescent Disorders: Empirically Based Strategies for Clinical Practice. 1996
DOI: 10.1037/10196-022
|View full text |Cite
|
Sign up to set email alerts
|

Learning experiences . . . an alternative program: Peer-mediated interventions for young children with autism.

Abstract: Peer-mediated interventions for young children with autism have, as their theoretical foundation, the notions that: (a) peers can be as or perhaps more effective than direct adult intervention agents; (b) for many skill domains, the contexts created by peer-mediated interventions are closer to the everyday, clinically relevant environments where clients must ultimately be able to function; (c) the abundance of peers in most settings creates natural opportunities for clients to learn from multiple examples (a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Using a design similar to that of the Denver Model studies, these authors have demonstrated that developmental rates of treated children accelerated to normal levels, with significant gains in virtually all areas of development. Further, long-term followup results were positive, with almost 50% of children attending regular school classes (61). The most influential and provocative paper in the literature on early intervention in autism was published by Lovaas and colleagues (64).…”
Section: Early Intervention In Autismmentioning
confidence: 99%
“…Using a design similar to that of the Denver Model studies, these authors have demonstrated that developmental rates of treated children accelerated to normal levels, with significant gains in virtually all areas of development. Further, long-term followup results were positive, with almost 50% of children attending regular school classes (61). The most influential and provocative paper in the literature on early intervention in autism was published by Lovaas and colleagues (64).…”
Section: Early Intervention In Autismmentioning
confidence: 99%
“…As reflected by the concerns raised about the changes in the DSM-5, including diminished sensitivity of the diagnostic criteria for young children (Barton et al 2013;Frazier et al 2011;Gibbs et al 2012), there is not a current consensus within the field on the boundaries or symptom clusters of autism. However, the importance of early detection and intervention for children with ASD and their relationship with positive outcomes has been well established (Howlin, 1998;Lord & McGee, 2001;MacDonald, Parry-Cruwys, Dupere, & Ahearn, 2014;Rogers & DiLalla, 1991;Rogers, Herbison, Lewis, Pantone, & Reis, 1986;Rogers & Lewis, 1989;Schopler, Reicheler, Bashford, Lansing, & Marcus, 1990;Strain, Kohler, & Goldstein, 1996).…”
Section: List Of Tablesmentioning
confidence: 99%
“…Infants demonstrate joint attention by following, checking, and directing others' gaze to objects. Sharing emotional states can be seen in the desire to share one's own emotions with another by directing emotional expressions purposefully to the partner's face; it is also seen in social or emotional referencing: when the infant checks the partner's face for emotional cues and then behaves accordingly in an ambiguous or unsettling situation [Stern, 1985].…”
Section: Intersubjectivitymentioning
confidence: 99%
“…Drawing from earlier work [Trevarthen and Hubley, 1978;Bruner, 1975], Stern [1985] used the term ''intersubjectivity'' to refer to behaviors first seen in the 9-12-month-old infant's seeming awareness of shared mental states. Several different behaviors reflect a new capacity for intersubjectivity: sharing intentions, sharing joint attention, and sharing emotional states.…”
Section: Intersubjectivitymentioning
confidence: 99%